Effect of Physical Exercise on Fatigue in Cervical Cancer Patients - Fatwa Imelda; Nur Afi Darti; Farida Linda Sari Siregar (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
Cervical cancer is the first female health problem in Indonesia with a high mortality rate. Fatigue is a common problem in patients with cervical cancer, fatigue due to cancer is different from fatigue of normal people. One of the self-empowerment recommended for managing post-therapy fatigue is physical exercise. Objective: to examine the effect of physical exercise on fatigue in cervical cancer patients. Metods: a quasy-experimental research with pretest-posttest with control group design was used. Thirty-four respondents were selected using purposive sampling in this study, which 17 respondents were randomly assigned in the experiment and control group. The Piper Fatigue Scale (PFS) was used to measure fatigue level. Paired t-test and Independent t-test were used for data analysis. Results: there was a significant effect of physical exercise on the decrease of fatigue levels in cervical cancer patients with p-value 0.000 (p<0.05), t= -5.794. Conclusion: physical exercise can be recommended in reducing fatigue levels in patients with cervical cancer.